2014
DOI: 10.1117/1.jbo.19.1.016019
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive near-infrared fluorescent protein-based imaging of tumor progression and metastases in deep organs and intraosseous tissues

Abstract: Abstract. Whole-body imaging of experimental tumor growth is more feasible within the near-infrared (NIR) optical window because of the highest transparency of mammalian tissues within this wavelength spectrum, mainly due to improved tissue penetration and lower autofluorescence. We took advantage from the recently cloned infrared fluorescent protein (iRFP) together with a human immunodeficiency virus (HIV)-based lentiviral vector to produce virally transduced tumor cells that permanently express this protein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…Proteins of the iRFP series enabled visualization of small tumors at early stages, monitoring tumor growth and tracking metastases [13, 31]. In particular, iRFP713 protein performed well as a fluorescent marker in tumors located in deep organs, such as liver and prostate, and intrabone tumors, such as intracranial glioblastoma and intratibial osteosarcoma (Figure 2a) [32]. Using various imaging modalities (Figure 3) iRFP713 enabled imaging progression of inflammatory breast cancer and its metastases in lymph nodes [33] and detection metastatic targets of melanoma in whole body (Figure 3b) [32].…”
Section: Biological Applications Of Near-infrared Fluorescent Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins of the iRFP series enabled visualization of small tumors at early stages, monitoring tumor growth and tracking metastases [13, 31]. In particular, iRFP713 protein performed well as a fluorescent marker in tumors located in deep organs, such as liver and prostate, and intrabone tumors, such as intracranial glioblastoma and intratibial osteosarcoma (Figure 2a) [32]. Using various imaging modalities (Figure 3) iRFP713 enabled imaging progression of inflammatory breast cancer and its metastases in lymph nodes [33] and detection metastatic targets of melanoma in whole body (Figure 3b) [32].…”
Section: Biological Applications Of Near-infrared Fluorescent Proteinsmentioning
confidence: 99%
“…In particular, iRFP713 protein performed well as a fluorescent marker in tumors located in deep organs, such as liver and prostate, and intrabone tumors, such as intracranial glioblastoma and intratibial osteosarcoma (Figure 2a) [32]. Using various imaging modalities (Figure 3) iRFP713 enabled imaging progression of inflammatory breast cancer and its metastases in lymph nodes [33] and detection metastatic targets of melanoma in whole body (Figure 3b) [32]. iRFP713 also allowed to monitor tumor growth and metastases in an orthotopic prostate cancer model (Figure 3f) [31, 34].…”
Section: Biological Applications Of Near-infrared Fluorescent Proteinsmentioning
confidence: 99%
“…As shown in Supplementary Figure 2, lifetime multiplexing enables the detection of approximately 1400 subcutaneous MTLn3-iRFP720 cells. This should be compared to the previously reported detection threshold of 5×10 4 subcutaneous iRFP cells using continuous wave fluorescence imaging (13). …”
Section: Resultsmentioning
confidence: 90%
“…A major challenge for the application of iRFPs to whole-body imaging of small and deep seated disease is their relatively low molecular brightness, which implies that tissue AF can still remain a significant contributor to the fluorescent signal. Although whole-animal imaging of iRFP-labeled tumors has been demonstrated (9,12,13), the tumors in these studies were either subcutaneous or consisted of several million cells in deep tissue. The ability to detect smaller metastases in deep organs of whole animals is of far more significance for pre-clinical oncology studies (14), since it will allow optimization of drug treatments to control the disease in its earliest stages.…”
Section: Introductionmentioning
confidence: 99%
“…While use of EGFP and DsRed may be useful in in vitro studies, they may not be as attractive in fluorescence imaging of deep tumors due to limited penetration of light, tissue absorption and scattering. Recently, Jiguet-Jiglaire et al (2014), reported the use of an infrared fluorescent protein with fluorescence characteristics laying within a near IR transparency of mammalian tissues 78 . This approach helped overcome issues related to fluorescent light tissue penetration, absorption and scattering in small animals such as mice facilitating more reliable preclinical studies; however, the application of this approach in larger animals or humans has not been investigated yet.…”
Section: Tracking the Stem Cellsmentioning
confidence: 99%